The silver chair - Lewis, C.S.; The Chronicles of Narnia (Lahore ILQA Publications, 2015)
Although less than a year has passed on Earth, it s been like ages in Narnia since (3z(BThe Voyage of the Dawn Treader.(3y (BKing Caspian X has grown old and his only son, Prince Rilian, has been missing for some years. Eustace Scrubb and his classmate Jill Pole sneak into Aslan s Country through a gate on Earth and Aslan blows them off to Narnia to find the missing prince. Jill is new to Narnia and though she has signs from Aslan, will she be able to help Eustace find Rilian? (3z(BThe Silver Chair(3y (Bis 6th Narnian novel.s
A classic of children s fantasy literature, (3z(BThe Chronicles of Narnia(3y (Bis a series of seven stand-alone books. It is one of the most popular children series ever written. It has been translated in more than 40 languages and sold over 100 million copies around the worlds
Keywords: Adventure Books, Adventure Books, Classic Books & Novels, Contemporary & General Fiction, Children Fantasy & Sci-Fi, Children Fiction & Stories, Classic Books, Novels & Novelettes